(untitled) (Educological discourse, 2015)
It is analyzed the integrated approach to the pedagogic researches in the English-speaking scientific community; it is characterized the modern pedagogical conceptions such as: productive pedagogy, authentic pedagogy, inquiry based pedagogy model and multiliteracies pedagogical model.